PENGARUH UMUR SEMBELIH TERHADAP KARAKTERISTIK KARKAS MUSCOPY DUCK (CAIRINIA MOSCHATA) - Harapin Hafid; Engki ENGKIZELPINA; Siti Hadrayanti Ananda (Jurnal Peternakan Nusantara, 2025)
This study aims to determine the effect of slaughter age on the carcass characteristics of Muscovy ducks (Cairina moschata). The research at the Laboratory of Animal Science and Production Technology, Faculty of Animal Husbandry, Halu Oleo University. A total of 20 male Muscovy ducks were randomly selected from a farm in Cialam Jaya Village, Konda Sub-district, South Konawe Regency. The study was designed using a completely randomized design with four treatments and five replications. The age treatments included ducks aged 6 months (P1), 12 months (P2), 18 months (P3), and 24 months (P4). Before slaughter, the ducks were fasted to minimize bias from digestive tract contents, and their live weights were measured. Halal slaughtering was conducted by severing the esophagus, trachea, jugular vein, and common carotid artery. After complete bloodletting, the ducks were scalded in hot water to facilitate feather removal. This was followed by evisceration and separation of the head, neck, and feet to obtain the carcass. The carcass was weighed and divided into parts: breast, thigh, back, and wing, which were then individually weighed. The observed variables included slaughter weight, carcass percentage, and percentages of carcass parts such as the breast, thigh, back, and wing. The results showed that age significantly affected carcass percentage and the percentage of carcass parts, including thighs, breasts, and wings, but had no significant effect on slaughter weight or the percentage of the back. It was concluded that as the age of the ducks increased, so did the carcass percentage and the percentages of carcass parts, particularly the breast and thigh.An abstract is a concise summary for readers to get a general understanding on the research conducted. It is written in a formal English in accordance with the guidelines of scientific paper writing. Each abstract and abstrak is written in a full paragraph of no more than 250 words of 10 font size without any reference, table, or figure. It should include problems to be solved, objectives, methods, results, and conclusions. However, an abstract should not contain excessive figures. No shortened words are allowed except for those which will be used more than once.